An Investigation of the Glossary of Khaghani Sherwani’s Book of Poems - Hashem Sadeghi Mohsenabad; Akbar Heidariyan (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
This study aimed to investigate the descriptive glossary of Khaghani Sherwani’s book of poems written by Rasoul Chehrghani. Successful glossaries, to some extent, have been published about Khaghani Sherwani’s book of poems, before this work. Thus, this glossary has tried to make some new points on ignored issues in previous glossaries and shed elucidatory light on the complex poems. In addition to discussing the general features of this work and analyzing its structural features, its merits, drawbacks, and content requirements were also analyzed. The book under study was analyzed for the content mistakes at two levels: structural and formal analysis. Moreover, it was found that the reliability of the work under study was significantly decreased due to disregard for new research findings, the lack of consideration of some punctuation marks, incorrect entries, inconsistencies of entries and descriptions, the lack of use of primary sources, and mistakes as a result of the hasty publication process. Finally, some suggestions were made to improve the quality of the book.